Impacts of Drying and Rewetting on the Radiocarbon Signature of Respired CO2 and Implications for Incubating Archived Soils. Issue 9 (14th September 2021) - Beem‐Miller, Jeffrey; Schrumpf, Marion; Hoyt, Alison M.; Guggenberger, Georg; Trumbore, Susan
Abstract: The radiocarbon signature of respired CO2 (∆ 14 C‐CO2 ) measured in laboratory soil incubations integrates contributions from soil carbon pools with a wide range of ages, making it a powerful model constraint. Incubating archived soils enriched by "bomb‐C" from mid‐20th century nuclear weapons testing would be even more powerful as it would enable us to trace this pulse over time. However, air‐drying and subsequent rewetting of archived soils, as well as storage duration, may alter the relative contribution to respiration from soil carbon pools with different cycling rates. We designed three experiments to assess air‐drying and rewetting effects on ∆ 14 C‐CO2 with constant storage duration (Experiment 1), without storage (Experiment 2), and with variable storage duration (Experiment 3). We found that air‐drying and rewetting led to small but significant ( α  < 0.05) shifts in ∆ 14 C‐CO2 relative to undried controls in all experiments, with grassland soils responding more strongly than forest soils. Storage duration (4–14 y) did not have a substantial effect. Mean differences (95% CIs) for experiments 1, 2, and 3 were: 23.3‰ (±6.6), 19.6‰ (±10.3), and 29.3‰ (±29.1) for grassland soils, versus −11.6‰ (±4.1), 12.7‰ (±8.5), and −24.2‰ (±13.2) for forest soils. Our results indicate that air‐drying and rewetting soils mobilizes a slightly older pool of carbon that would otherwise be inaccessible to microbes, an effect that persists throughout the incubation. However, as the bias in ∆ 14 C‐CO2 from air‐drying and rewetting is small, measuring ∆ 14 C‐CO2 in incubations of archived soils appears to be a promising technique for constraining soil carbon models. Plain Language Summary: Soils play a key role in the global carbon cycle by sequestering carbon from the atmosphere for decades to millennia. However, it is unclear if they will continue to do so as the climate changes. Microbial decomposition of soil organic matter returns carbon back to the atmosphere, and radiocarbon dating of this returning CO2 (∆ 14 C‐CO2 ) can be used to quantify how long carbon is stored in ecosystems. Incubating archived soils could provide unique insight into soil carbon sequestration potential by quantifying the change in ∆ 14 C‐CO2 over time. However, air‐drying, duration of archiving, and subsequent rewetting of soils may bias estimates of sequestration potential by altering the balance of younger versus older carbon leaving the soil. We compared ∆ 14 C‐CO2 from soils incubated with and without air‐drying and archiving, and found that the air‐dried soils appeared to release slightly older carbon than soils that had never been air‐dried. The amount of time the soils were archived did not have an effect. Since the bias from air‐drying and rewetting was small, incubating archived soils appears to be a promising technique for improving our ability to model soil carbon cycling under global climate change. Key Points: ∆ 14 C of CO2 measured in incubations of archived soils provides additional constraints for soil carbon models Air‐drying and rewetting soils shifted the ∆ 14 C of respired CO2 by 10‰–20‰ independent of the duration of storage Differences in direction and magnitude of ∆ 14 C‐CO2 shifts between forests and grasslands depended on sampling year and system C dynamics